Christmas time at Special Spot Day Care - Watkins, Howard::::::::: (1981)
Howard Watkins as Santa Claus with Adam Watkins, Sandy Jones, Devon Bleile-Kratzer, Marshall Chambers, and holding arm of Seth Tilley